Studi Kajian Realisasi Pendapatan Pemerintah Daerah Kabupaten Deli Serdang - Putri Alifa Dafina; Lidya Permata Sari; Anaya Rezeki Salsabila; Lucya Br. Manik; Rusiadi Rusiadi; Dewi Mahrani Rangkuty (Jurnal Kajian dan Penelitian Umum, 2023)
. Local revenue also plays a role in implementing regional government planning to develop development and improve a region’s economy. This study examines the realization of local government revenue in Deli Serdang Regency. This descriptive qualitative study uses the literature method through literature studies supported by secondary data from the progress report on the development control of North Sumatra Province. The results of the study state that local government revenue is a prosperous capital in achieving regional development goals because it determines the region’s capacity to carry out government functions. The higher and more significant the revenue received, the area is declared capable of showing independence to finance all obligations towards regional development.